Sosialisasi Perencanaan Bisnis pada Mahasiswa Perguruan Tinggi di Kota Banjarmasin - Henidinia Tricahya; Rizka Ramadhani; Abdul Majid Habibi; Anna Nur Faidah; Sudirwo Sudirwo (Lembaga Pengembangan Kinerja Dosen, 2025)
Business planning and business development are crucial steps to maintain business continuity and progress in a highly competitive market environment. Business planning refers to the systematic formulation of strategies to achieve a company's long-term growth goals. This includes identifying opportunities and challenges in the market, designing strategies for marketing and sales, human resource development, and innovation and technology analysis, and environmental sustainability management. The purpose of this planning is to produce clear and organized guidelines so that the company can achieve its long-term vision and objectives. The methodology used in this study is qualitative descriptive which aims to describe the phenomena surrounding business planning and development. This planning process is also important for detecting risks, improving operational efficiency, and ensuring business continuity in the future.